Woman By. - Spruyt, Maarten; Ex, Sjarel; Ferwerda, Jetty; Jonkers, Gert; Teunissen, José (Utrecht : Centraal Museum Utrecht, 2003)
Antistrot ; Demeulemeester, Ann ; Chalayan, Hussein ; Freudenthal, Carmen ; Verhagen, Elle ; Frik, Helen ; Galliano, John ; De Groot, Kaleb ; Van Harreveld, Kate ; Huntelaar, Yolanda ; Jeroense, Peter ; Jonkers, Gert ; Klap, Roosje ; Leroy, Veronique ; Margiela, Martin ; Mascia, Pierre-Louis ; Marshall, Adam ; Papazoglou, Evangelos ; Spaans, Dieuwke ; Spruyt, Maarten ; Viktor & Rolf ; Watanabe, Junya ; Westwood, Vivienne ; Willhelm, Bernhard
biog. p. 156-158
WOMAN, Centraal Museum, Utrecht, van 1 februari t/m 18 mei 2003
boek